2015
DOI: 10.1109/tap.2015.2392125
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of High-Order Impedance Boundary Conditions in Some Integral Equation Formulations

Abstract: The scattering problem from an object coated with materials is solved in the frequency domain. The coating is modeled by an impedance boundary condition (IBC) implemented in an integral equation (IE) prescribed on its outer surface. The Leontovich IBC (IBC0) is local and constitutes a poor approximation for low index coatings. A possible remedy is to employ higher order IBCs. These, as well as the IBC0, are implemented in two IE formulations: 1) CFIE with the electric current as sole unknown and 2) EFIE+MFIE w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…For a thin monolayer of thickness d, effective and well-posed high order IBCs (HOIBCs) of order k have been obtained via a multiscale asymptotic expansion of the exact solution with respect to d [2][3][4], and it has been mathematically and numerically demonstrated that, if Γ is smooth enough, the error between this expansion and the exact solution scales as O(d k+1 ). Regarding a low index and not necessarily thin multilayer, essentially heuristic HOIBCs involving tangential derivatives of the tangent electric and magnetic fields on Γ are available in the literature [5][6][7][8][9][10][11][12][13]. A generalized IBC was first proposed in the space domain for 2-D problems [5] where the coefficients in the IBC are derived from the exact reflection coefficient calculated for a plane wave incident on a planar layer.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…For a thin monolayer of thickness d, effective and well-posed high order IBCs (HOIBCs) of order k have been obtained via a multiscale asymptotic expansion of the exact solution with respect to d [2][3][4], and it has been mathematically and numerically demonstrated that, if Γ is smooth enough, the error between this expansion and the exact solution scales as O(d k+1 ). Regarding a low index and not necessarily thin multilayer, essentially heuristic HOIBCs involving tangential derivatives of the tangent electric and magnetic fields on Γ are available in the literature [5][6][7][8][9][10][11][12][13]. A generalized IBC was first proposed in the space domain for 2-D problems [5] where the coefficients in the IBC are derived from the exact reflection coefficient calculated for a plane wave incident on a planar layer.…”
Section: Introductionmentioning
confidence: 99%
“…In the spectral domain (infinite plane or 2D circular cylinder) an effective HOIBC with five coefficients has been proposed in [7] where the IBC coefficients are calculated in such a way as to yield an impedance as close as possible to the exact one (local planar or cylindrical approximation: LPA or LCA) in a large angular range including evanescent incident waves, and this HOIBC has been successfully applied to axisymmetric bodies [7]. A corresponding space domain formulation, termed here IBC3, has been proposed in [8] that can be applied to arbitrary 3D objects, and has been numerically implemented in MoM formulations [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our numerical examples indicate that the third order IBC consistently gives the most accurate results up to a value of δ = 0.09. Important numerical evaluations concerning high order impedance boundary conditions are performed also in many references, we cite, e.g., [17,28,29].…”
Section: Introductionmentioning
confidence: 99%